Two- and Three-Dimensional Transesophageal Echocardiographic Interrogation of an Atrial Septal Pouch Thrombosis. Issue 9 (1st November 2018) - Williams, Emily; Anthony, David; Duncan, Andra
Abstract : Supplemental Digital Content is available in the text.